Why consider quantum instead classical pattern recognition techniques? - Barreto, Artur Gomes; Fanchini, Felipe Fernandes [UNESP]; Papa, João Paulo [UNESP]; de Albuquerque, Victor Hugo C. (Elsevier, 2024)
This article delves into the evolving landscape of pattern recognition, transitioning from classical methodologies to quantum-based techniques. It underscores how quantum algorithms offer a new paradigm with the potential to overcome the limitations of classical techniques. Unlike conventional methods, which, while effective, often struggle with complex and high-dimensional datasets, quantum algorithms are poised to surpass these limitations. This study explores the applications, benefits, drawbacks, and open issues surrounding quantum pattern recognition methods and provides a comprehensive overview of the current state of quantum technology and outlines potential future directions, highlighting the intersection of quantum computing and pattern recognition for breakthroughs.
Keywords: Quantum algorithms; Quantum computing; Quantum computing applications; Quantum datasets; Quantum machine learning